Effects of orthotropy and variation of Poisson's ratio on the behaviour of tubes in pure flexure - Wadee,MK; Wadee,MA; Bassom,AP (J MECH PHYS SOLIDS, 2007)
The behaviour of tubes under conditions of pure bending is investigated for the cases where the material of which they are constructed is either orthotropic or of various Poisson's ratios. Large deflections and moderate nonlinear strains are considered and the modelling incorporates Timoshenko beam theory thereby allowing non-zero shear strains to develop. This in turn makes axially inhomogeneous deformation of the cross-section possible and, in particular, the compressed side can develop wrinkling. Numerical solutions are presented for various material types and tube dimensions and some interesting phenomena, such as mode interaction and jumping, are demonstrated. (C) 2006 Elsevier Ltd. All rights reserved.